Visual information management (London, 1995)
The book provides a comprehensive survey of visual interfaces, image and video data management, and data visualization. Firstly, the visual management of data is discussed, from the theoretical background to descriptions of several user interfaces based on the most advanced interaction techniques. Secondly, the management of multimedia data, in particular images and video, is analysed, with emphasis on querying by content. Finally, advanced visualization techniques are examined
Keywords: visual programming ( computer science )